Dampak Kebijakan Otonomi Daerah Terhadap Pemberdayaan Masyarakat Lokal - Rohim, Annisa (Postgraduate Program Doctoral in Law, Universitas Pattimura, 2024)
Introduction: Regional autonomy gives regional governments more authority in managing local resources and policies. This has the potential to strengthen community empowerment by increasing participation, access to public services, and more effective local economic management. However, challenges such as inequality and lack of local capacity are still obstacles in realizing this potential. Purposes of the Research: It is hoped that this study will provide a clearer picture of the successes and challenges faced in implementing regional autonomy, as well as provide recommendations for increasing the effectiveness of this policy in empowering local communities more optimally. Methods of the Research: This research method uses a normative approach with literature study, reviewing journals, books and other sources to analyze the impact of regional autonomy policies on empowering local communities, as well as the legal and social implications they cause. Results of the Research: This research reveals that regional autonomy policies have a significant impact on the empowerment of local communities. On the one hand, decentralization allows local governments to be more responsive to local needs and optimize regional resource potential. However, on the other hand, the implementation of this policy is sometimes hampered by the lack of local government capacity in managing resources and lack of coordination between agencies. However, in several regions, regional autonomy has succeeded in increasing community participation in decision making and strengthening local economic capacity, which ultimately supports community welfare and strengthens social resilience at the local level.